HUBUNGAN ANTARA KUALITAS LAYANAN PARAMEDIK DAN KEPUASAN PASIEN RAWAT JALAN DI PUSKESMAS TANAH LUAS ACEH UTARA TAHUN 2019 - Diana Sinulingga; Safwati Safwati; Sentosa Barus (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2020)
Measurement of the patient satisfaction level is crucial in an effort to improve the quality of health services. The measurement aims to visualize whether health services that have been provided could fulfil the expectations and satisfaction of patients. This Study was quantitative analytical survey with a cross sectional approach which aims to analyze the relationship betfween the quality of health care services and outpatient satisfaction in public health center of Tanah Luas of North Aceh in 2019. The population of study as outpatient Departmant who went to the publichealth center, Tanah Luas of North Aceh. The total population was 17.479 people and the sample was 96 people recruited with a purposive sampling technique. Data analysis used chi-square and logistic regression test. Data collection was done by using primary data questionnaires, as well as secondary data. the results of the study showed that reliability, comprehension, assurance, empathy and direct evidence had significant relationship with outpatient satisfaction. the most influencing factor is direct evidence factor. It is suggested for the health center to evaluate the performance of health workers, officers as well as doctors periodically to improving the service and to keep being friendly when providing services to the patients. Recommendation for the next researcheso that r to do the structured interviews beside using questionnaires to evaluate and analyze further causes and reasons related to factors that influence patient satisfaction to find the deepen results.